'By sharing work we are moving forward':change in social norms around men's participation in unpaid care work in Northern Uganda. (2nd January 2021) - Rost, Lucia Aline
ABSTRACT: There has been increasing interest in understanding gendered social norms and how they change. This paper explores change in social norms relating to men's participation in unpaid care work in Northern Uganda, where mixed-methods data from adults, children and adolescents was collected. Socio-cultural changes, related to a civil war and other influences, have been observed in this region. This paper finds that some men took on more responsibility for care work and described this as socially acceptable where it involved 'masculine tools', was perceived to be 'modern' or to bring financial benefits. These subtle adjustments do not cause radical change but are important because, over time, they can shift social norms in a more permanent way.